Soil phosphorus saturation ratio for risk assessment in land use systems - Nair, Vimala D. (Frontiers in Environmental Science, 2014)
The risk of phosphorus loss from agricultural soils can have serious implications for water quality. This problem has been noted particularly in sandy soils in several parts of the world including Europe (e.g., the Netherlands, Italy, and UK) and the southeastern USA. However, the capacity of a soil to retain P is limited and even non-sandy soils have the potential to eventually release P when inorganic or organic fertilizer is added over a period of time. A threshold phosphorus saturation ratio (PSR), calculated from P, Fe and Al in an oxalate or a soil test solution such as Mehlich 1 or Mehlich 3, has been recognized as a practical means of determining when a soil has reached a level of P loading that constitutes an environmental risk. When soils are below a threshold PSR value, the equilibrium P concentration (EPC0) is minimal. Further, the soil P storage capacity calculated from the same data is directly linked to the strength of P bonding (KL) as determined from Langmuir isotherms, and KD, the distribution coefficient related to the strength of sorption. While the PSR is occasionally used as a predictor of the onset of environmentally significant P loss from a soil, the procedure might be adopted as a routine soil test.